Late sodium current inhibitors to treat exercise‐induced obstruction in hypertrophic cardiomyopathy: an in vitro study in human myocardium. (3rd May 2018) - Ferrantini, Cecilia; Pioner, Josè Manuel; Mazzoni, Luca; Gentile, Francesca; Tosi, Benedetta; Rossi, Alessandra; Belardinelli, Luiz; Tesi, Chiara; Palandri, Chiara; Matucci, Rosanna; Cerbai, Elisabetta; Olivotto, Iacopo; et al.
Abstract : Background and Purpose: In 30–40% of hypertrophic cardiomyopathy (HCM) patients, symptomatic left ventricular (LV) outflow gradients develop only during exercise due to catecholamine‐induced LV hypercontractility (inducible obstruction). Negative inotropic pharmacological options are limited to β‐blockers or disopyramide, with low efficacy and tolerability. We assessed the potential of late sodium current (INaL )‐inhibitors to treat inducible obstruction in HCM. Experimental Approach: The electrophysiological and mechanical responses to β‐adrenoceptor stimulation were studied in human myocardium from HCM and control patients. Effects of INaL ‐inhibitors (ranolazine and GS‐967) in HCM samples were investigated under conditions simulating rest and exercise. Key Results: In cardiomyocytes and trabeculae from 18 surgical septal samples of patients with obstruction, the selective INaL ‐inhibitor GS‐967 (0.5 μM) hastened twitch kinetics, decreased diastolic [Ca 2+ ] and shortened action potentials, matching the effects of ranolazine (10μM). Mechanical responses to isoprenaline (inotropic and lusitropic) were comparable in HCM and control myocardium. However, isoprenaline prolonged action potentials in HCM myocardium, while it shortened them in controls. Unlike disopyramide, neither GS‐967 nor ranolazine reduced force at rest. However, in the presence of isoprenaline, they reduced Ca 2+ ‐transient amplitude and twitch tension, while the acceleration of relaxation was maintained. INaL ‐inhibitors were more effective than disopyramide in reducing contractility during exercise. Finally, INaL ‐inhibitors abolished arrhythmias induced by isoprenaline. Conclusions and Implications: Ranolazine and GS‐967 reduced septal myocardium tension during simulated exercise in vitro and therefore have the potential to ameliorate symptoms caused by inducible obstruction in HCM patients, with some advantages over disopyramide and β‐blockers.